Motivasi Guru Madrasah Ibtida’iyah - Imam Suraji (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This research is a qualitative phenomenological study that aimed to describe the motivation of Madrasah Ibtidaiyah teachers in Pekalongan regarding their teaching activities. Data were collected through in-depth interviews, participant observation, and documentation. The data were analyzed using the interactive model developed by Miles and Huberman. The results showed that the informants believed that teaching is a blessed (berkah) profession, which motivated them to become teachers. At the same time, they also hoped to receive a sufficient salary (berkat) from their profession. The combination of teachers’ beliefs about the blessings (berkah) of the teaching profession and their hopes of earning an adequate income (berkat) encourages them to carry out their duties seriously.